SEMIOTIKA ROLAND BARTHES SEBAGAI PENDEKATAN UNTUK MENGKAJI LOGO KANTOR POS - Ahmad Riyadi Swandhani; Deddy Wahjudi; Lukitaningsih Lukitaningsih (Gorga : Jurnal Seni Rupa, 2023)
Semiotics is a language of signs, semiotics is widely used as a tool to translate something, one of which is the post office logo, the purpose of this study is to see how the semiotic language developed by Roland Barthes can represent the post office logo in the form of a bird and lines and colors. unified, Roland Barthes theorized semiotics is between signs and signs, besides that there are also levels in the meaning of this semiotic theory, this research approach is Semiotic analysis is a qualitative data analysis technique whose goal is to find or systematically analyze symbols or signs in a text , from the results of this study there is a distortion of myth, as a marker is a dove which has a meaning or a sign that a bird has a strong myth as a means of sending letters in historical times, so that the use of Roland Barthes' semiotics can analyze the semiotic language of a h the post office logo, the thing that must be emphasized is the important role of the reader, in the sense that the meaning of a work depends on the person who is of course influenced by many factors both internal and external.Keywords: semiotics, roland barthes, post office. AbstrakSemiotika merupakan Bahasa tanda, semiotika banyak digunakan sebagai alat untuk menerjemahkan sesuatu, salah satunya ialah logo kantor pos, tujuan penelitian ini ialah melihat bagaimana Bahasa semiotika yang di kembangkan oleh roland barthes ini, dapat merepresentasikkan logo kantor pos yang berupa burung dan garis Tarik serta warna yang tersatukkan , roland barthes berteori semiotika ialah antara tanda dan pertanda, disamping itu juga ada tingkatan dalam pemaknaan dari teori semiotika ini, pendekatan penelitian ini ialah Analisis semiotika adalah teknik analisis data kualitatif yang tujuannya untuk menemukan atau menganalisis secara sistematis simbol atau tanda dalam sebuah teks, dari hasil peneltian ini terdapat distorsi pada mitos, sebagai penanda ialah burung merpati yang memiliki makna  atau pertanda burung memiliki mitos yang kuat ikatannya sebagai alat pengiriman surat pada zaman sejarah, sehingga penggunaan semiotika roland barthes dapat menganalisis Bahasa semiotika dari sebuah logo kantor pos, hal yag harus ditekankan ialah pentingnya peran dari pembaca, dalam artian pemaknaan suatu karya tergantung dari personal yang tentunya dipengaruhi oleh banyak faktor baik internal ataupun eksternal.Kata Kunci: semiotika, roland barthes, kantor pos. Authors:Ahmad Riyadi Swandhani : Institut Teknologi BandungDeddy Wahjudi : Institut Teknologi BandungLukitaningsih : Universitas Negeri MedanReferences:Aulia, F., Afriawan, H., & Faisal, D. (2022). Konsistensi Logo Dalam Membangun Sistem Indentitas. Gorga: Jurnal Seni Rupa,11(2), 439-444.Barthes, R. (1964). Rhetoric of the Image. Communication 4, 40-51.Barthes, R. (1967). Element of Semiology. New York: Hill & Wang.Barthes, R. (1972). Mytholgies: New York The Noonday Press Cooper, J.C (2013). An Illustrated Encyclopedia of Traditional Symbols. London: Thames & Hudson.Barthes, R. (2010). Membedah Mitos-Mitos Budaya Massa. Yogyakarta: Jalasutra.Saussure, F. D. (1988). Course in General Linguistics. Yogyakarta: Gajah Mada Univesity Press.Direktorat Jendral Pos dan Telekomunikasi. (1980). Sejarah Pos dan Telekomunikasi di Indonesia Jilid IV Masa Demokrasi Terpimpin. Jakarta: Cahaya Makmur.Gunalan, S., & Hasbullah, H. (2020). Analisis pemaknaan semiotika pada karya iklan layanan masyarakat. Jurnal Nawala Visual, 2(2), 44-51. https://doi.org/10.35886/nawalavisual.v2i2.117.Gunalan, S., Haryono, H., & Yasa, I. N. M. (2022). Analisis Pemaknaan dan Tanda Pada Desain Logo GP Mandalika Series. Gorga: Jurnal Seni Rupa, 11(1), 212-219. https://doi.org/10.24114/gr.v11i1.34285Hartoko, D. (1991). Manusia dan Seni. Jakarta: Kansius.Khairi, A. I., & Hafiz, A. (2022). Kajian Estetika Lukisan Realis Kontemporer Drs. Irwan, M. Sn. yang Berjudul di Ujung Tanduk. Gorga: Jurnal Seni Rupa, 11(1), 138-146. https://doi.org/10.24114/gr.v11i2.39802.Liliweri, A. (2003). Dasar-Dasar Komunikasi Antar Budaya. Yogyakarta : Pustaka Pelajar.Linschoten, J., & Mansyur. (1983). Pengantar Ilmu Jiwa. Bandung: Jemmars.Miswar, M., Rian, R., Muler, Y., & Rajudin, R. Studi Warna Dan Gaya Pada Karya Yazid. Gorga: Jurnal Seni Rupa, 11(2), 370-378. https://doi.org/10.24114/gr.v11i2.38384.Mudjiyanto, B., & Nur, E. (2013). Semiotics In Research Method of Communication [Semiotika Dalam Metode Penelitian Komunikasi]. Jurnal Pekommas, 16(1), 73-82. https://doi.org/10.30818/jpkm.2013.1160108.Piliang, Y. A. (2004). Semiotika Teks: Sebuah Pendekatan Analisis Teks. Mediator: Jurnal Komunikasi, 5(2), 189-198. https://doi.org/10.29313/mediator.v5i2.1156.Prang, L. (1876). The Theory of Colour. Boston: Massachusetts.Purbasari, M., & Jakti, R. A. (2014). Warna Dingin Si Pemberi Nyaman. Humaniora 5(1), 357. https://doi.org/10.29313/mediator.v5i2.1156.Richards, J., Platt, J., & Weber , H. (1985). Longman Dictionary of Applied Linguistics. Harlow: Longman.Rustan, S. (2009). Mendesain Logo. Jakarta: PT Gramedia Pustaka Utama.Tinarbuko, & Sumbo. (2008). Semiotika Komunikasi Visual. Yogyakarta: Jalasutra.Zakiy, R. A. (2020). Analisis Semiotika Iklan Cetak LA Lights "Jangan mau diadu" Versi Ayam. Gorga: Jurnal Seni Rupa, 9(2), 232-235. https://doi.org/10.24114/gr.v9i2.19551.